On demand dynamic linkage control system for air volume of multiple coal working faces - YANG Xu; ZHANG Lang; MA Qiang; LIU Yanqing; ZHANG Hongjie; ZHAO Kaikai; LI Wei; DUAN Sigong; GENG Feng (Gong-kuang zidonghua, 2022)
When multiple coal working faces are mined at the same time in the coal mine, the change of branch air volume of any roadway will cause the change of branch air volume of other roadway. The air volume control of any coal working face in the mine will affect the air volume change of other coal working faces in the mine. Therefore, it is necessary to intelligently control the air volume of multiple coal working faces. However, the current research on intelligent control of air volume in coal working face is mainly based on automatic control algorithm of mine air volume or mine air volume control equipment. It lacks the research on the on demand dynamic linkage control system for air volume of multiple coal working faces. In order to solve the above problems, this paper puts forward a design scheme of on demand dynamic linkage control system for air volume of multiple coal working faces. Taking the louvered remote automatic regulating air window deployed in the return air crossheading of 3308 working face in Shanxi Tiandi Wangpo Coal Industry as the research object, the computational fluid dynamics (CFD) method is used to simulate the flow field distribution of the regulating air window. The Origin software is applied to fit the non-linear relationship between the wind area of the regulating air window and the wind resistance, and obtain the functional relationship between them. The relative error between the wind resistance of the regulating air window measured on site and that calculated by fitting is less than 6%. Based on the functional relationship between the wind area and the air resistance of the regulating air window and a joint calculation method of wind resistance regulation of multiple coal working faces, the upper computer calculation software is developed. And based on the upper computer calculation software, the underground explosion-proof and intrinsically safe control substation and the louvered remote automatic regulating air window, the on demand dynamic linkage control system for air volume of multiple coal working faces is constructed. The on demand dynamic linkage control of air volume on demand is carried out on 3308 and 3203 coal working faces in Wangpo Coal Industry. The field application shows that the relative error between the target air volume and the actual air volume after control is less than 7%. This result indicates that the on-demand dynamic linkage control system for air volume of multiple coal working faces has certain use effect.